Mother–Child Reminiscing About Peer Experiences and Children's Peer‐related Self‐views and Social Competence. Issue 2 (19th December 2012) - Song, Qingfang; Wang, Qi
Abstract: This study examined mother–child reminiscing about children's experiences with peers and its relation to children's peer‐related self‐views and social competence. Sixty‐three mothers and their preschool‐aged children discussed at home two specific past events involving the child and his or her peers, one event being positive and one negative. The children's self‐views in peer relationships were assessed at school during individual interviews, and their social competence was rated by mothers. Both maternal and child participation in the reminiscing, in terms of reminiscing style and content, were uniquely associated with children's peer‐related self‐views and social competence. The results suggest the important role of family narrative practices in children's social development.